STRATEGI WKS KURIKULUM DALAM KEEFEKTIVAN BELAJAR MELALUI TEAM GROUPING PESERTA DIDIK DI SMP PLUS DARUSSALAM BLOKAGUNG - Zainul Mun’im; Hany Aury Anggraini (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2022)
The objectives set in this study are: (1) to find out how the WKS Curriculum strategy is in Effective Learning through Student Grouping Teams at SMP Plus Darussalam Blokagung for the 2021/2022 academic year; (2) to find out what are the inhibiting factors for the implementation of the Student Grouping Team learning model at SMP Plus Darussalam Blokagung for the 2021/2022 academic year. This research method uses descriptive qualitative. Collecting data through interviews, observation, and documentation. There are four research subjects, namely the principal, WKS curriculum, one subject teacher, and two students. Data analysis using SWOT analysis. The data validity technique uses triangulation. Research results: The strategies obtained through SWOT analysis are: (1) With good communication students can solve problems quickly, team grouping discipline, mutual cooperation, and responsibility can provide maximum results in groups. (2) There is socialization from the curriculum so that teachers pay more attention to students when grouping activities take place, there is direct guidance from teachers to students who are not serious in team grouping activities. (3) With the existence of a group leader, it is hoped that they can be responsible for whether or not their group members can, each group is expected to create a comfortable atmosphere in the group so that teaching and learning can run smoothly. (4) Maintaining an attitude of responsibility, mutual cooperation, and discipline in team grouping, maintaining good communication between students in team grouping groups.